PENEGAKAN KODE ETIK PROFESI POLRI TERHADAP ANGGOTA KEPOLISIAN YANG TERLIBAT PENYALAHGUNAAN NARKOTIKA - Zikir Irwanda Syaputra; Bagio Kadaryanto; Sandra Dewi (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIH Awang Long, 2025)
The purpose of this study is to analyze the enforcement, obstacles, and efforts to overcome these obstacles in the Indonesian National Police's code of ethics against officers involved in drug abuse within the jurisdiction of the Riau Regional Police. The method used was sociological legal research. The results indicate that enforcement of the Indonesian National Police's code of ethics against officers involved in drug abuse within the jurisdiction of the Riau Regional Police is carried out firmly and in layers through an internal oversight mechanism involving the Propam (Propam), Paminal (Minimal), Provos (Provos), and Wabprof (Deputy for Professional Development). The author found that any officer suspected of using narcotics was immediately subjected to initial examination, urine tests, internal arrests, and a track record of involvement was traced. Observations also showed that the ethics enforcement process was transparent and formal. In the field, it is evident that the Indonesian National Police (Polri) applies the same standards to all members without exception, and imposes sanctions ranging from coaching, demotion, special placement, to dishonorable discharge for serious violations. This demonstrates the institution's commitment to maintaining discipline, integrity, and public trust in the government. Obstacles appear to stem from structural, technical, and cultural factors. This is exacerbated by the uncooperative attitude of some members during inspections, some even trying to avoid, refuse summons, or manipulate statements. Efforts are being made through several strategic steps. First, improving discipline and internal oversight functions under the coordination of the Propam Division. Second, tightening internal inspection mechanisms, including surprise urine tests for members in units deemed vulnerable. Third, the author observed efforts to strengthen the mental and spiritual development system as part of a prevention strategy. Furthermore, there is a commitment to expediting the code of ethics review process to avoid delays that could potentially reduce the deterrent effect against violations.